2022
DOI: 10.3389/fpls.2022.835380
|View full text |Cite
|
Sign up to set email alerts
|

Shade Delayed Flowering Phenology and Decreased Reproductive Growth of Medicago sativa L.

Abstract: Alfalfa (Medicago sativa L.) is an important forage in intercropping or rotation ecosystem, and shading is the principal limiting factor for its growth under the crop or forest. Agronomic studies showed that shading would systematically reduce the biomass of alfalfa. However, little is known about the reproduction of alfalfa under shading conditions. In order to study the effect of shading on the reproductive characteristics of alfalfa, two alfalfa cultivars (“Victoria” and “Eureka”) were used to study the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…As a perennial forage, alfalfa dwells in meadowlands ( Wang et al., 2009 ; Guo et al., 2016a ), where populations grow in full sunlight. However, alfalfa can also be distributed under canopies of forest trees ( Qin et al., 2022 ). Light is a fatal factor that may limit the growth and development of undergrowth ( Zhao et al., 2020 ; Chu et al., 2021 ; Song et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a perennial forage, alfalfa dwells in meadowlands ( Wang et al., 2009 ; Guo et al., 2016a ), where populations grow in full sunlight. However, alfalfa can also be distributed under canopies of forest trees ( Qin et al., 2022 ). Light is a fatal factor that may limit the growth and development of undergrowth ( Zhao et al., 2020 ; Chu et al., 2021 ; Song et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Shade can systematically reduce biomass production in alfalfa, but the light deficit would not threaten survival in shading up to 50% ( Lin et al., 1998 ; Varella et al., 2001 ). It has also been found that shade limits the reproduction of alfalfa through the delay of flowering ( Lorenzo et al., 2019 ; Qin et al., 2022 ). Given that populations at the understory layer are subjected to the sunlight spectrum of transmittance ( Wei et al., 2019 ; Wei et al., 2020 ), the light spectrum is a determinative factor of illumination condition for plant growth and development ( Chu et al., 2021 ; Zhou et al., 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…Qin et al. (2022) discovered that high‐light intensity had the capacity to induce alfalfa to bloom. Our data corroborated these findings, as alfalfa subjected to light intensity treatments of 500 and 600 µmol m −2 s −1 entered the initial flowering stage on the 35th day.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of photosynthetic yield was found to be regulated by light intensity, thereby exerting a subsequent influence on the differentiation of flower buds (Wen et al, 2021). Qin et al (2022) discovered that high-light intensity had the capacity to induce alfalfa to bloom. Our data corroborated these findings, as alfalfa subjected to light intensity treatments of 500 and 600 µmol m −2 s −1 entered the initial flowering stage on the 35th day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation